Retrospective analytical five months study of aortic arch abnormalities - Chelliah, Nellaiappan (International Journal of Research in Medical Sciences, 2016)
Background: Aortic arch abnormalities include congenital anomalies and acquired pathologies. Many of aortic arch congenital anomalies are asymptomatic lesions. But some of these anomalies are symptomatic and need to be treated. Radiological appearances should be familiar for these anomalies to the radiologist for correct interpretation. Aortic arch abnormalities reported in our institute are analysed in this article. Methods: This is a retrospective analytical study of five months from July 2015 to October 2015. The study was carried in the radiodiagnosis department of tirunelveli medical college hospital. In our institute, 494 cases of Computerised tomography (CT) Chest scans have been taken in above period for various conditions. In which Patients with vascular abnormalities of aortic arch in the scan were selected for the study i.e. sample selection. No of patients selected for analysis are 20. They have undergone CT scan, Magnetic resonance angiography (MRI) scan. Those findings were analysed and hereby are presented, in which age varied as low as 1 year and as high as 78 years. Results: Most of aortic arch abnormality cases belong to age group 60-80. About 75% of aortic abnormalities are acquired. The aortic arch abnormalities are commoner in males than females especially acquired diseases of aorta. Rare cases of Double aortic arch, aberrant right subclavian artery with dissection of aorta are diagnosed in these patients. Conclusions: It is noted that acquired conditions are the commonest abnormalities. CT scan and MRI complement each other. MR angiogram gives definitive diagnosis in aortic arch abnormalities. Double aortic arch is most common symptomatic vascular ring. MRI is the best single imaging study for the diagnosis and characterization of vascular rings. Aortic dissection needs urgent imaging. Multislice CT, MRI has replaced conventional angiogram.